Penawaran Tenaga Kerja Pertanian dan Perubahannya: Studi Kasus pada Usahatani Padi di Beberapa Desa Jawa Barat - Sumaryanto, nFN (Jurnal Agro Ekonomi, 1990)
Understanding labor supply behaviour of the rural people is the primary condition to improve their welfare. This study utilized panel data as a basis of analysis. Those data was taken from the survey conducted in 1977 and 1983 using the same household sample. The results showed that factors influencing labor supply in the farm activity are real wage, farm size, type of labor arrangement, and agro ecosystem. Lower growth rate of farm labor wage than non farm labor wage coupled with better access of rural household to non farm activity significantly reduced elasticity of labor supply in the farm sector. Moreover, the increase on factor share accruing to land and the decrease on labor share accentuated the negative impact of sawah land holding to labor supply.